A ‘Better Resurrection’ (Hebrews 11.35), but Better Than What? - Brown, J. Tyler (Journal for the study of the New Testament, 2025)
Nearly all agree that the ‘better resurrection’ (κρείττων ἀνάστασις) of Heb. 11.35 refers to the eschatological, general resurrection, but the majority view that it is to be compared merely with the resuscitations of the women’s sons by Elijah and Elisha stands on weaker foundations than is usually recognized. Building on Jon Levenson’s work on ancient, scriptural notions of death and resurrection (2006), the article shows through a close reading of Heb. 11.35 in context that the ‘better resurrection’ is compared most immediately with the ‘redemption’ from captivity the verse’s Maccabean martyrs reject, i.e., a temporary return to life understood as a kind of resurrection, but also with the resuscitations of the faithful women’s sons. Together with the resurrection of Isaac ‘in a symbol’ (ἐν παραβολῇ, 11.19), this conclusion suggests that Hebrews’ catalogue of Israel’s heroes is marked throughout by the proleptic experience of resurrection from the invasive realm of death.